1995
DOI: 10.1111/j.1432-1033.1995.0498e.x
|View full text |Cite
|
Sign up to set email alerts
|

Octanoate Affects 2,4‐Dinitrophenol Uncoupling in Intact Isolated Rat Hepatocytes

Abstract: When intact isolated rat hepatocytes, either incubated or perifused, were uncoupled by 2,4‐dinitrophenol, we found that the effect on glucose and lactate+pyruvate fluxes, cytosolic and mitochondrial redox states and ATP/ADP ratios were dependent on the nature of the exogenous substrate added. 2,4‐Dinitro‐phenol addition (0.25 mmol/1) to cells perifused with dihydroxyacetone (10 mmol/1) resulted in a modest and transient activation of oxygen uptake accompanied by a surprising rise in lactate/pyruvate ratio indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…DNP, as an uncoupler of OXPHOS, decreases ROS production via the electron transport chain (Okuda et al, 1992;Korshunov et al, 1997) and modulates nicotinamide adenine dinucleotide (phosphate) ratios (NAD(P) H-to-NAD(P) ratio) (Sibille et al, 1995;Leverve et al, 1998;Rex et al, 1999;Hoffmann et al, 2001), thereby altering the cellular redox state to increase ATP production by glycolysis (O'Fallon and Wright 1986;Hewitson et al, 1996). Conflicting reports exist as to whether or not DNP benefits development, though.…”
Section: Discussionmentioning
confidence: 99%
“…DNP, as an uncoupler of OXPHOS, decreases ROS production via the electron transport chain (Okuda et al, 1992;Korshunov et al, 1997) and modulates nicotinamide adenine dinucleotide (phosphate) ratios (NAD(P) H-to-NAD(P) ratio) (Sibille et al, 1995;Leverve et al, 1998;Rex et al, 1999;Hoffmann et al, 2001), thereby altering the cellular redox state to increase ATP production by glycolysis (O'Fallon and Wright 1986;Hewitson et al, 1996). Conflicting reports exist as to whether or not DNP benefits development, though.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect of 2,4-dNP-induced mild mitochondrial uncoupling is the increased cost of mitochondrial ATP production that could ultimately decrease the cellular availability of ATP (Sibille et al, 1995;Geelen et al, 2008). In this context, there would be three main cellular ways to compensate for the reduced mitochondrial ATP resulting from 2,4-dNP treatment: activation of glycolysis, mitochondrial biogenesis and/or increase of the oxidative phosphorylation capacity of individual mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic 2,4-dNP exposure at a low dose is expected to induce mild mitochondrial uncoupling (Wallace and Starkov, 2000). Consequently, the treatment could have a beneficial effect on oxidative stress and decrease the cellular availability of ATP (Sibille et al, 1995;Wallace and Starkov, 2000;da Silva et al, 2008;Geelen et al, 2008). There are three main ways to compensate for the reduced mitochondrial ATP production: (i) activation of the glycolytic pathway, (ii) increased mitochondrial biogenesis, and (iii) increased oxidative phosphorylation capacity of individual mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, specifically designed (eco)toxicological studies with known uncouplers as the stressors, such as exposure–recovery tests, knockout–rescue tests, and blockage–continuation tests, as well as modulation–response tests, were used to evaluate the essentiality of key events. The essentiality of the MIE (Event 1446: Decrease, Coupling of OXPHOS) is considered high, because direct evidence was collected from multiple specifically designed studies showing simultaneous recovery of OXPHOS coupling (as indicated by the membrane potential) and ATP pool due to removal of the uncouplers (see Weisová et al, 2012), or addition of OXPHOS recoupling agents (see Sibille et al, 1995). The essentiality of KE1 ( Event 1771: Decrease, ATP pool ) is considered high, as supported by direct evidence from a typical inhibition–rescue study showing restimulation of cell proliferation by ATP (Wang et al, 2017) and multiple lines of indirect evidence showing strong positive correlations between ATP and cell proliferation (see Sweet & Singh, 1999).…”
Section: Summary Of Scientific Evidence Assessmentmentioning
confidence: 99%